Performance criteria and design of shallow foundation of an arched steel bridge on liquefiable soil - Gkioka, Maria (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής. Εργαστήριο Μεταλλικών Κατασκευών, 2015)
In the current thesis the response of an arch steel bridge on liquefiable soil to imposed differential settlements and rotations, as well as the innovative design of a shallow foundation for the pier of the bridge are investigated. The conventional approach to the phenomenon of liquefaction is to use pile foundation, so that the loads of the superstructure can be transferred to deeper, non-liquefiable soil layers with adequate strength. In the proposed innovative solution, the concept of a shallow foundation is investigated, assuming that the liquefiable soil functions as a seismic isolator. A positive outcome that derives from the use of a shallow foundation on liquefiable soil is the decrease of the seismic actions that reach the pier and the superstructure. However, due to liquefaction, additional permanent ground movements, by means of settlements and rotations may evolve after a major earthquake event. The behavior of the bridge is investigated in order to determine the permissible ground movements, which would not result in the loss of its serviceability and strength. These permissible settlements and rotations are used for the design of the pier footing. To that end, the pier response to combined rotations and settlements, which simulate the differential displacements caused by liquefaction, is investigated. The bridge under investigation consists of two simply supported spans, 42.00m each, which are connected through a continuity slab, 1m long. The theoretical width of the deck is 14.70. A composite deck is employed and each span consists of two main beams and seventeen transverse beams. Each main beam is suspended by a corresponding arch with seven hangers, while the two arches of each span are interconnected with transverse and diagonal bracing members. The height of the arches reaches 10m. The main beams, the transverse beams, the arches and the bracing members are made of structural steel. The pier consists of a concrete beam and three reinforced concrete columns, thus forming an indeterminate frame with a height of 10m, including the concrete beam. The abutments are considered rigid. The numerical model of the bridge is developed with the use of the finite element analysis software ADINA v8.5. Nonlinear static analyses are conducted, taking into account the nonlinearities of the geometry, the material and the initial imperfections of the steel members. Bending moment – curvature diagrams have been used to simulate the non linear behavior of the RC columns of the pier. Special attention was given to the investigation of the in- and out-of-plane buckling of the steel members of the superstructure. To achieve the latter, a dense finite element mesh was used for these members, and initial imperfections were considered. In order to define the shape of the initial imperfections, a Linearized Buckling Analysis (LBA) was conducted, so as to establish the buckling modes. Subsequently, a combination of these buckling modes is used, to take into account the possible buckling types of the steel members. Then, nonlinear static analyses are conducted, where combined settlements and rotations are imposed at the base of the pier. At the end of these analyses, the behavior of all crucial members, including the steel members of the superstructure, the bearings and the pier, is recorded up to first failure. The first failure is defined as the first yield at the base of the pier columns, the formation of plastic hinges at the top of the pier columns, or the failure of main steel members. The failure of the bearings, the continuity slab, or the diagonal bracing members is not considered important, since these members cannot provoke the collapse of the bridge and can be easily repaired or replaced. Therefore, they are not crucial for the determination of the permissible displacements of the soil. However, the alteration of their stiffness is taken into account, in case they exceed yield or bearing damage. Simultaneously, the response of the concrete beam of the pier is not investigated, since it is considered almost rigid and does not affect the permissible settlements and rotations. The analyses indicated that the rotation about the longitudinal axis of the bridge is the most crucial one, as it results in plastic hinges at the top of the pier columns. Correspondingly, the rotation about the transverse axis of the bridge provokes significant bending moments at the base of the pier columns, thus rendering the yield at these positions crucial. However, no failure is observed at the steel members, although the diagonal bracing moments are subject to buckling in some analyses. Moreover, no damages are observed at the bearings. The smallest permissible settlement value that the bridge can withstand without significant, irreparable damages leading to collapse, is equal to ρmax=24cm, while the combined rotation about a random axis equals θmax=0.05ρmax=1.2ο. Considering that the bridge has already been subjected to settlements and rotations due to liquefaction caused by a major seismic event, the response of the bridge to a second earthquake is investigated. The earthquake that provokes liquefaction (Seismic Scenario 2) has a significant return period (T=1000), with a magnitude of M=7.0. Due to the natural seismic isolation offered by the liquefied soil, this earthquake does not cause large internal forces on the structure. However, liquefaction results in permanent settlements and rotations that are developed at the base of the pier, at the end of the major seismic event, which increase the bending moments on the columns of the pier. Such a large earthquake is unlikely to happen again within the life span of the bridge, therefore an earthquake with a smaller return period equal to T=225 years and a magnitude of M=6.2 (Seismic Scenario 1) is expected, which does not cause liquefaction and therefore the natural seismic isolation is not employed. Thus, the bridge under investigation having been subjected to permanent displacements (settlements and rotations) at the base of the pier due to Seismic Scenario 2, is subjected to a second earthquake and the permissible percentage of the design earthquake (Seismic Scenario 1) is established, with respect to maintaining the performance levels of the bridge. The analyses indicate that, if the displacements of the footing, expected by the geotechnical report, are taken into account, the percentage of the design earthquake, the bridge can withstand without significant damages, reaches 70% of Seismic Scenario 1. The diploma thesis has been conducted within the research project “THALIS”, entitled “Innovative Design of Bridge Piers on Liquefiable Soils with the use of Natural Seismic Isolation”, performed under the general coordination of Professor George Bouckovalas.